Kant’s Errors. Rosmini’s Critique of Kant’s Transcendental Idealism (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The article analyses Rosmini’s critique of Kant’s philosophy. The authoraludes to the criticism of Kant as a question of principles that criticizes Kant’ssubjectivism and the wrong formulation of the ideological problem (of the origin of ideas) related to the synthetic a priori judgments. Ending by holding that Kantconfuses predicates with attributes, concepts with things, and leads his philosophy to subjectivism.
Keywords: Being; feeling; knowledge.